The ECCOMAT Program for the Selection of Ecological Materials in Order to Ensure a Healthy Built Environment. (2015) - Aciu, Claudiu; Manea, Daniela Lucia; Striletchi, Cosmin
Abstract: The quality of the indoor environment is a determining factor for health due to fact that people spend most of their lives inside the buildings. In the current context, the entire construction industry is confronted with particular priorities regarding the execution of sustainable buildings. Designers and constructors have become increasingly aware of the wide spectrum of issues that affect the environment and health, but they face a confusing number of possible actions and solutions, which makes the selection of materials difficult. The paper presents the calculation program developed based on the ECCOMAT analysis method, which is a tool designed to offer the users multiple possibilities for the management and analysis of building materials, helping them obtain in an easy and rapid way the optimal solution. The application field is the design and construction of buildings with ecological materials and the extension of research in order to obtain new ecological materials.